Pengaruh Kompetensi Digital dan Pelatihan Kerja terhadap Kinerja Karyawan pada PT. Pos Indonesia (Persero) Regional VI Makassar 90004 - Muh Juniar Elfarid; Muchriady Muchran; Nurinaya Nurinaya (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the influence of digital competencies and on-the-job training on employee performance at PT. Pos Indonesia Regional VI Makassar 90004. The study employs a quantitative approach using a causal-associative research design to examine the relationship between the independent and dependent variables. The sample consisted of 57 respondents representing the entire population of employees. Data collection was conducted through the distribution of questionnaires using a Likert scale to measure respondents’ perceptions regarding digital competencies, on-the-job training, and employee performance. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that digital competencies and on-the-job training have a positive and significant influence on employee performance, both partially and simultaneously. Employees with better digital capabilities and adequate job training tend to demonstrate higher levels of effectiveness, productivity, and work quality. These findings indicate that strengthening digital competencies and implementing sustainable on-the-job training programs are essential strategies for improving employee performance amid the challenges of digital transformation. Therefore, companies are encouraged to continuously develop employee digital skills and provide relevant training programs to support organizational performance and competitiveness.